UJI TERHADAP RELIABILITAS DAN RELEVANSI LAPORAN KEUANGAN EMITEN DI INDONESIA STOCK EXCHANGE - Ranteallo, Asrah Tandirerung; Rosento, Rosento (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2018)
This study is to examine whether the financial statements made by the issuer have provided reliable and relevant information. Investors, securities sales agents and creditors are the respondents who will answer the questionnaire. The respondents were asked to comment on the reliability and relevance of the company's financial statements used as the basis for their decision making. The research sample was selected randomly based on the group of financial report users who periodically use the issuer's financial statements in Indonesia Stock Exchange (IDX) for decision making. questionnaires were sent to 200 respondents. There were 50 respondents' answers that were analyzed using the match pairs sign test method. The results showed that the issuer's financial statements on IDX tended to present information that was less relevant but the user considered that the accounting information presented was still reliable.